OKOKAN TRADITION: UNDERSTANDING NOBLE VALUE IN THE FRAME OF SYMBOLIC INTERACTIONALISM - Riza Wulandari; I Gusti Ayu Widari Upadani; Salman Alfarisi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Purpose: This study aims to explore the meaning of the noble value of the Okokan Art tradition in the Village of Kediri, Tabanan, Bali Province by using the symbolic interactionism point of view. Research methods: The case studies are used as a method in discussing symbolic interactions that occur in the Okokan tradition performers. Results and discussions: Based on the results of scientific studies in the field, it was found that the Okokan tradition is a form of representation of noble values in each symbolic such as the representation of seeking safety to Sang Hyang Widhi through the offerings of the performer, the noble value of the work ethic in the manifestation of dance movements, the attributes imposed reflecting the noble values of human nature to always harmonious, and the representation of folklore displayed is the harmony of humans and nature. Conclusion: Symbolic interaction in the Okokan tradition is a representation of the noble values that exist in Kediri Village, Tabanan, Bali, Indonesia.